2005
DOI: 10.1111/j.1440-1746.2005.04048.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and management of antituberculosis drug induced hepatotoxicity

Abstract: Periodic laboratory monitoring is important in detecting hepatotoxicity at an early stage, thereby preventing mortality. Sequential reintroduction is often successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 26 publications
3
50
0
2
Order By: Relevance
“…Five patients (13.2%) with anti-TB DIH death during TB treatment, one of them was diagnosed acute liver failure due to anti-TB DIH. The mortality rate in this study was similar to the study that conducted by Agal et al with mortality rate of 16.6% [20]. The other prospective study showed that none of TB patients with DIH was death from group TB patient that performed routine monitoring liver function.…”
Section: Discussionsupporting
confidence: 89%
“…Five patients (13.2%) with anti-TB DIH death during TB treatment, one of them was diagnosed acute liver failure due to anti-TB DIH. The mortality rate in this study was similar to the study that conducted by Agal et al with mortality rate of 16.6% [20]. The other prospective study showed that none of TB patients with DIH was death from group TB patient that performed routine monitoring liver function.…”
Section: Discussionsupporting
confidence: 89%
“…Early identification may offer scope for applying interventions to improve prognosis. Other studies have confirmed such benefit of regular monitoring [46,47] . Rapid increase of ALT implies need to investigate viral hepatitis and toxicity to any other drugs and more frequent monitoring, e.g.…”
Section: Conclusion and Epiloguementioning
confidence: 62%
“…The frequency of hepatotoxicity varies from 2 to 28% in different populations and occurs even when the drug has been given at the recommended doses (Tostmann et al, 2008). Approximately 9.5% of Indian patients have been reported to develop antitubercular therapy (ATT)-induced hepatotoxicity (Agal et al, 2005). This often results in discontinuation of the most effective first-line drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Non-compliance not only leads to morbidity and mortality but also results in the emergence of drug-resistant strains. Majority of ATT-induced hepatotoxicity incidences are evident in the first month of treatment for a combination of RIF and INH but can occur up to the third month when PYZ is combined (Agal et al, 2005).…”
Section: Introductionmentioning
confidence: 99%